Pengaruh Orientasi Kewirausahaan dan Sistem Informasi Akuntansi Menggunakan Startegi Bisnis Sebagai Variabel Moderasi Pada UKM Kabupaten Banyumas - Widianingsih, Rini; Sunarmo, Agus (Jurnal Indonesia Sosial Sains, 2022)
The purpose of this study was to determine and analyze the effect of entrepreneurial orientation and accounting information systems on SME performance and the role of business strategy in moderating the effect of entrepreneurial orientation and accounting information systems on SME performance in . Banyumas Regency Government to determine and analyze the area. This research method is a survey with data analysis techniques using moderate regression analysis. As a result of this study, entrepreneurial orientation and accounting information systems have a positive effect on SME outcomes, and business strategy does not strengthen the effect of entrepreneurial orientation on outcomes, and business strategy strengthens the effect of accounting information systems on SME outcomes. in the government of Banyumas.